Analisis Kelayakan Ekonomi Prototipe Rempeyek Berbasis Kulit Buah Naga untuk Valorisasi Agroindustri Skala UMKM - Retno Sari Mahanani; M. Farukh Muniruzzaman; Akbar Maulana Firmansyah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2026)
Utilizing agricultural waste is a strategic agenda to support economic, environmental, and social sustainability. Dragon fruit peel, an abundant agricultural waste, remains underutilized as a raw material for value-added products. Meanwhile, empirical studies integrating dragon fruit peel waste-based product development with economic feasibility analysis at the micro-enterprise scale are limited. This study aims to analyze the feasibility of a dragon fruit peel-based food product at a pilot scale. This research was conducted as an experimental research and development (R&D) study in Jember, focusing on the development of a rempeyek product prototype. The production process was designed to be simple and replicable by Micro, Small, and Medium Enterprises (MSMEs) using standard kitchen equipment. Primary data related to production inputs, time, and costs were analyzed to assess operational and economic feasibility. The results showed that the pilot production was operationally feasible with an output of 25 packages per batch. The economic analysis yielded a R/C ratio of 1.40, a positive Return on Investment (ROI) of 9.54% per batch, and a break-even point of 18 packages. The novelty of this research lies in the presentation of a product development model based on dragon fruit peel waste that has been operationally and economically tested at the MSME scale.